PENGARUH BEBERAPA INOKULUM SPESIES FUNGI MIKORIZA ARBUSKULAR TERHADAP PERTUMBUHAN SEMAI JABON (Anthocephalus cadamba Roxb.) - Annadira, Annadira; Yusran, Yusran; Irmasari, Irmasari (Jurnal Warta Rimba, 2014)
Jabon is a plant that is being developed because including fast growing spesies, Jabon an Indonesian native spesies wich valuable high economic and have qualities that do not compote with other spesies . Jabon is a spesies of seed that can be developed trough industri plantation forest and community forest but the aspect of cultivation in the nursery often experience barries in maintenance for example wilting occurs that causes death. This research aimed to know the effect of some inoculum species of FMA ( Fungi Micorrhizal Arbucular) on the growth of jabon (Anthocephalus cadamba Roxb) seedlings. The research was conducted at green house, Forestry Faculty, Tadulako University from Desember 2013 to February 2014. The study was laid out in a Randomized Complete Design (RCD)Â  with four threatments, i.e : Control/without treatment (M0), Glomus mosseae (M1), Glomus clorum (M2), and Glomus deserticola (M3). The observation parameters consits of seedling height increment, diameter increment, leaf number increment, fress weight of roots and shoots, dry weight of roots and shoots and seedling quality index. The result showed that inoculation of FMA spesies significantly affected seedling growth of A. cadamba Roxb. Generally Glomus mosseae spesies was highly improves seedling of A. cadamba Roxb compared to Glomus clorum, and Glomus deserticola spesies and control. Keywords: Â FMA (Fungi Micorrhizal Arbuscular), Jabon (Anthocephalus cadamba Roxb.), Seedling growth